Konsep Lembaga Negara Indonesia dalam Perspektif Teori Trias Politica Berdasarkan Prinsip Checks and Balances System - Suparman, Odang (AHKAM, 2023)
There have been many constitutional law experts who have made studies and at the same time thoroughly investigated various legal studies and have been used as a reference for a world figure named Baron Secondat de Montesquieu (hereinafter known as Montesquieu) with his famous theory built and developed, namely the Triassic Theory Politica. The theory of Trias Politica in its implementation, if applied, is still relevant in the development of the constitutional era and is one of the pillars of democracy. Based on the Theory of Trias Politica, in principle, dividing state political power into three State Institutions, namely: 1. Legislature; 2. Executive; and 3. Judiciary. In order to realize the three types of State Institutions that are independent of each other and are in an equal rank (horizontal) to one another. The equality and independence of these three types of State Institutions is and is necessary so that the three state institutions can or are willing and able to supervise and control each other based on the principle of a checks and balances system in practice. The separation and division of the three authorities in three different State Institutions, it is hoped that the running of the state government will not be unequal and at the same time not overlapping, and can avoid Collusion, Corruption and Nepotism (KKN) government by one Institution and at the same time will bring up a checks mechanism and balances system (correcting and balancing each other). Power according to the Theory of Trias Politica into three parts can be explained in this study.